Systematic analysis of the burden of chronic kidney disease due to type 2 diabetes attributable to dietary risks based on the global burden of disease study 2021 - Hou, Yanli; Qin, Lingzhi; Jin, Xuting; Ren, Jiajia; Li, Jiamei; Zhang, Xiaoling; Zhang, Jingjing; Li, Ruohan; Gao, Ya; Wang, Xiaochuang; Wang, Gang (Frontiers in Nutrition, 2025)
BackgroundDietary factors play a crucial role in the development of chronic kidney disease due to diabetes mellitus type 2 (T2D-related CKD). However, comprehensive data on the global burden of T2D-related CKD attributable to dietary risks remain limited.MethodsThis study conducted a secondary analysis of the Global Burden of Diseases, Injuries, and Risk Factors Study 2021. Mortality and disability-adjusted life years (DALYs) of T2D-related CKD attributable to dietary risks, stratified by sex, age and sociodemographic index (SDI) quantiles, were analyzed in global, 21 regions, and 204 countries and territories from 1990 to 2021.ResultsIn 2021, 79,990 (95% confidence interval [CI]: 32,730–128,880) death and 1,999,210 (95% CI: 856,190–3,167,220) DALYs of T2D-related CKD were attributable to dietary risk factors, approximately 2.5 times as many as those in 1990. The age-standardized mortality rate (ASMR) and age-standardized DALY rate (ASDR) grew with an estimated annual percentage change (EAPC) of 0.76% (95%CI: 0.69–0.83%) and 0.47% (95%CI: 0.41–0.53%). The low SDI regions experienced the highest burden of T2D-related CKD attributable to dietary risks, with ASMR of 1.16 (95% CI: 0.44–2.02) per 100,000 persons and the ASDR of 27.41 (95% CI: 11.32–46.78) per 100,000 persons. Males and the elderly over 70 years demonstrated a higher burden of T2D-related CKD influenced by dietary risks. Diet low in fruits, whole grains, and vegetables, as well as diet high in red and processed meat serve as the main dietary risks contributed to the burden of T2D-related CKD.ConclusionDietary factors play a significant role in the development of T2D-related CKD. Further strategies should focus on men, the elderly, low-SDI regions and specific dietary components to mitigate dietary risks associated with T2D-related CKD.